Molecular detection of Rickettsia genus in chigger mites (Trombidiformes: Trombiculidae) collected on small mammals in southeastern Brazilian - De Castro Jacinavicius, Fernando; Bassini-Silva, Ricardo; Muñoz-Leal, Sebastián; Welbourn, Cal; Ochoa, Ronald; Labruna, Marcelo Bahia; Barros-Battesti, Darci Moraes [UNESP] (FapUNIFESP (SciELO), 2019)
Chiggers are ectoparasites of vertebrates and may cause trombiculiasis or transmit pathogens to their hosts. Specimens collected from rodents and marsupials were morphologically identified as Herpetacarus hertigi, Eutrombicula tinami, Kymocta sp., Quadraseta brasiliensis, Quadraseta falconensis, Quadraseta flochi, Quadraseta mackenziei, Quadraseta pazca, Quadraseta trapezoides, Quadraseta sp., Serratacarus sp., and Trombewingia bakeri. These mites were submitted individually to molecular analyses for the detection of bacteria of the genus Coxiella, Hepatozoon and Rickettsia. Samples were positive to Rickettsia only. Obtained sequences for the gltA (350 pb) and ompA (488 pb) genes were identical to “Candidatus Rickettsia colombianensi”, a species previously detected in ticks. In addition, molecular identification of mites based on 18S rDNA sequences are provided for H. hertigi, Kymocta sp., Q. brasiliensis, Q. pazca, Q. trapezoides, Quadraseta sp., and T. bakeri for the first time. This is the first report of the detection of a Rickettsia sp. in chigger mites collected on rodents in Brazil.
Detecção molecular do gênero Rickettsia em ácaros trombiculídeos (Trombidiformes: Trombiculidae) coletados em pequenos mamíferos do sudeste Brasileiro
Keywords: Brazil; Candidatus Rickettsia colombianensi; Chiggers; Didelphimorphia; Ectoparasites; Rodentia